BORROWED NEW TERMS IN THE TEACHER’S PROFESSIONAL COMMUNICATION - Дика, Наталія; Глазова, Олександра (SWorldJournal, 2025)
The article highlights the problem of borrowing new terms in the professional communication of teachers. It is emphasized that a significant increase in the dynamics of the use of neologisms was caused by the reform of Ukrainian education. For this reaso